Excusing child offenders: a victim justice perspective - Aprilianda, Nurini; Ansori, Ansori; Maharani, Febrianika (Faculty of Law, University of Muhammadiyah Malang, 2024)
This paper aims to explore the essence of the excuse defense for child offenders and justice for victims. In uncovering its meaning, doctrinal research is conducted with a legislative and conceptual approach, accompanied by a teleological interpretation of legal materials. The research findings indicate that the excuse defense is granted to children under the age of 12 who commit criminal offenses not because their actions are forgiven but due to their inability to form intent or comprehend the consequences of their actions. On the other hand, victims, as the injured party, must also receive justice. The author believes that the government should reconsider the application of the excuse defense for children. The government must also be more selective in determining appropriate sanctions for children based on the nature of the crime committed. If the child's actions result in significant material or immaterial harm, restorative justice may serve as a viable option to balance the interests of both parties, restore the victim's situation, and divert the child from judicial proceedings, thereby achieving a win-win solution.